2012
DOI: 10.1063/1.4712598
|View full text |Cite
|
Sign up to set email alerts
|

Antiferromagnetic domain wall engineering in chromium films

Abstract: We have engineered an antiferromagnetic domain wall by utilizing a magnetic frustration effect of a thin iron cap layer deposited on a chromium film. Through lithography and wet etching we selectively remove areas of the Fe cap layer to form a patterned ferromagnetic mask over the Cr film. Removing the Fe locally removes magnetic frustration in userdefined regions of the Cr film. We present x-ray microdiffraction microscopy results confirming the formation of a 90° spin-density wave propagation domain wall in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…[52,53] The domain wall structures have been observed in both types of antiferromagnetic materials [53][54][55], and can be effective controlled by using the exchange bias effects. [30,[56][57][58][59][60] Experimentally, it should be more straightforward to realize the spin wave polarizer and retarder proposed here using the synthetic antiferromagnetic wires used for the racetrack memory. [53] In conclusion, we demonstrated that the antiferromagnetic domain wall with Dzyaloshinskii-Moriya interaction naturally functions as a spin wave polarizer at low frequency, and a spin wave retarder (waveplate) at high frequency.…”
Section: Discussionmentioning
confidence: 99%
“…[52,53] The domain wall structures have been observed in both types of antiferromagnetic materials [53][54][55], and can be effective controlled by using the exchange bias effects. [30,[56][57][58][59][60] Experimentally, it should be more straightforward to realize the spin wave polarizer and retarder proposed here using the synthetic antiferromagnetic wires used for the racetrack memory. [53] In conclusion, we demonstrated that the antiferromagnetic domain wall with Dzyaloshinskii-Moriya interaction naturally functions as a spin wave polarizer at low frequency, and a spin wave retarder (waveplate) at high frequency.…”
Section: Discussionmentioning
confidence: 99%
“…Pinning sites for domain walls can arise from impurities or crystal defects in the underlying lattice of AFMs. Although several studies have found that pinning effects in AFMs are small, [57][58][59] dislocations and impurities diffuse the effects on a single spin. In quasi-one-dimensional spin chains the introduction of a single impurity atom can be enough to destroy long-ranged antiferromagnetic order and domain wall configurations.…”
Section: Effect Of Pinning Sites On Domain Wall Dynamicsmentioning
confidence: 97%
“…Antiferromagnetic domains [11] and several forms of domain wall (DW) structures in AFMs have been observed [12]. Furthermore, DWs in AFMs can also be induced, controlled and engineered by exchange bias pinning forces [3,13].Progress in the field of antiferromagnetic spintronics requires the development of novel methods for exciting AFMs at the nanoscale. Many AFMs are insulating and cannot be affected by currents in the bulk; however, other approaches can be employed to excite an AFM.…”
mentioning
confidence: 99%